Reliability and validity of the fixed-frame portable dynamometer in assessing ankle force sense in individuals with and without chronic ankle instability - Jianglong Zhan; Peng Chen; Zhongqi Yu; Teck Cheng Tan; Chaoyu Guo; Menghan Xu; Van Minh Le; Lin Wang (PLoS ONE, 2026)
Background Deficits in sagittal-plane ankle force sense impair the ankle strategy for counteracting perturbations and are associated with balance impairments in individuals with chronic ankle instability (CAI). However, standardized assessment devices, such as the CON-TREX dynamometry system, are expensive and impractical. In this study, a fixed-frame portable dynamometer (FF-PD) was developed, and its concurrent validity, discriminant validity, and test–retest inter-session reliability were evaluated in measuring ankle plantarflexion and dorsiflexion force sense in individuals with CAI, copers, and healthy controls. Methods A total of 72 participants (24 with CAI, 24 copers, and 24 healthy controls) performed force-matching tests utilizing the FF-PD and CON-TREX, and the FF-PD retested one week later. Concurrent validity was evaluated with Pearson correlations; discriminant validity, with one-way ANOVA and receiver operating characteristic (ROC) analyses; and reliability, with intraclass correlation coefficients (ICC), standard error of measurement (SEM), and minimal detectable change at the 95% confidence level (MDC 95 ). Results FF-PD exhibited moderate-to-strong correlations with CON-TREX ( r = 0.597–0.770, p ≤ 0.002). For discriminant validity, the FF-PD effectively distinguished individuals with CAI from healthy controls in plantarflexion ( p = 0.011) and dorsiflexion ( p = 0.034). ROC-derived cutoffs were 12.06% for plantarflexion and 9.57% for dorsiflexion. Test–retest inter-session reliability was good-to-excellent (ICC = 0.794–0.960), with low SEM (0.9%–2.6%) and clinically meaningful MDC 95 (2.5%–7.4%). Conclusion The FF-PD is a valid and reliable device for assessing ankle force sense in plantarflexion and dorsiflexion. It effectively differentiates individuals with CAI from healthy controls, and ROC-derived cutoff values provide clinically interpretable thresholds that may support clinical screening and decision-making, as well as the potential use in monitoring changes during clinical screening and rehabilitation.